CHARACTERISTICS AND NECESSITY OF DEVELOPING STUDENTS’ COMMUNICATIVE COMPETENCE (Scientific journal of the Fergana State University, 2023)
This article reveals the uniqueness and necessity of developing the communicative competence of students in teaching English, its components and the role of communicative competence in achieving quality education, as well as preparing students for communicative activities in later life. The issue of quality education is also considered, which is considered one of the main tasks of the educational process of a comprehensive school.